Knowledge and attitudes towards COVID-19 vaccines among university students, faculty members and staffs - Jomell Miranda Santiago; Angelo Reyes Santos (Intelektual Pustaka Media Utama, 2022)
One of the key strategies to stop the increase of coronavirus disease 2019 (COVID-19) cases is vaccines. The uncertainty and refusal of Filipinos to get the COVID-19 vaccine will be a crucial barrier to achieve the immunization coverage required for population protection. Thus, this study was conducted to determine the knowledge and attitude of the Nueva Ecija University of Science and Technology students and faculty and staff towards the COVID-19 vaccine. A descriptive study approach and total sampling were adopted. A questionnaire was constructed to accumulate data on the respondents' profile, knowledge, attitude and source of information about the vaccine for COVID-19. Informed consent and permission to conduct were acquired. Various statistical tools were used to analyze the data. The respondents were knowledgeable and had positive attitude towards the COVID-19 vaccine. Their primary source of information was from social media on the internet and television. There is a positive association between their attitude and knowledge of the COVID-19 vaccine, which means that they are closer to having a positive attitude when they are knowledgeable about the COVID-19 vaccine. Therefore, health education campaigns to increase their knowledge or awareness about the COVID-19 vaccine should encourage them to receive a COVID-19 vaccine shot.